Jehovah playing his part: A tale of giant hemangioma – Can we do major liver resections without blood or blood products? - Naragund, Adithya V; Kumar, Sharath S; Muddasetty, Rohith (Indian Journal of Case Reports, 2024)
Hemangiomas are common benign lesions of the liver. They are generally asymptomatic. Kasabach–Merritt syndrome is an uncommon presentation of hepatic hemangioma requiring treatment. Here, we present a case of a 26-year-old female of Jehovah’s Witness with large hepatic hemangioma and Kasabach–Merritt syndrome. She was refused surgery elsewhere due to the risk of intraoperative hemorrhage. With proper preoperative planning and a team approach, we have performed the successful resection of hemangioma without the need for blood transfusion. We present this case to convey that the use of low central venous pressure, hemodilution, meticulous surgical technique, and intraoperative blood cell salvage and autotransfusion can avoid allogeneic blood transfusion not only in Jehovah’s Witness but also in the general population.